Temporal changes in the ring seine fishery of Kerala, India - Das, P. H. Dhiju; Edwin, Leela (Indian Journal of Fisheries, 2018)
The marine fisheries of India is unique in that it is a typical multi-species, multi-gear tropical fisheries with a heterogeneous management system. Mini purse-seine (ring seine) was first introduced in the early eighties to enable the non-motorised traditional fisherman to counter the strongly emergent mechanised fishing in the state of Kerala. Ever since its introduction, there has been a phenomenal increase in the size and numbers of the fishing units and this fishing method has spread to other maritime states of the country. The present study analysed the evolution and growth of the ring seine fishing systems of central Kerala from 1985 to 2014. The economic and social impacts of the ring seine fishery were also studied and the findings emphasised the need for implementation of management measures to downscale the excess capacity in the fishery.